FACTORS AFFECTING HOUSEHOLD FOOD EXPENDITURE THROUGH THE UTILIZATION OF YARD LAND IN DEWANTARA SUBDISTRICT, ACEH UTARA : English - Martina, Martina; Praza, Riyandhi; Zuriani, Zuriani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
Food is a basic need that must be met by households. Utilization of home yard land is one of the alternatives to realize food self-sufficiency in households in Dewantara District which iscan save on food expenditure and ensure the fulfillment of household food needs which are always available, easily accessible and can be used at any time. This study aims to analyze the factors that influence household food expenditures that utilize yard land with horticultural cultivation in Dewantara Subdistrict, Aceh Utara. The sample in this study was 60 families who were selected by simple random sampling. Data were analyzed descriptively quantitatively using multiple linear regression test. The results showed that simultaneously the factorIncome (X1), yard area (X2), number of household members (X3), housewife education (X4), and number of working household members (X5) have a significant effect on food expenditure. Partially, only the income factor (X1) and the number of household members (X3) have a significant effect on household food expenditure.